Ischaemic conditioning reduces kidney injury in an experimental large-animal model of warm renal ischaemia. Issue 12 (12th August 2015) - Hunter, J P; Hosgood, S A; Barlow, A D; Nicholson, M L
Abstract: Background: Ischaemic conditioning, using short repeated sequences of intermittent ischaemia, is a strategy that may ameliorate ischaemia–reperfusion injury. The aim of the study was to assess the effects of direct and remote ischaemic conditioning in a porcine model of renal warm ischaemia–reperfusion injury. Methods: Pigs (50 kg) underwent laparotomy and 60-min occlusion of the left renal pedicle followed by right nephrectomy. Animals were divided into three groups: untreated controls ( n = 8); direct postconditioning involving six 15-s cycles of clamping then releasing of the left renal artery ( n = 7); or remote periconditioning involving four 5-min cycles of clamping then releasing of the left common iliac artery ( n = 8). After 7 days kidney tissue was harvested, and blood and urine samples were collected on postoperative days 1, 3 and 7. Results: The direct postconditioning group had a lower area under the serum creatinine curve (mean(s.d.) 1378(157) versus 2001(1022) µmol/l · day respectively; P = 0·036) and peak creatinine level (316(46) versus 501(253) µmol/l respectively; P = 0·033) compared with values in control animals. There was a significant increase in serum levels of tumour necrosis factor α on day 1 in control animals but not in the conditioning groups ( P = 0·013). Urinary levels of neutrophil gelatinase-associated lipocalin increased over the study period in both the control and remote groups ( P = 0·001 for both), but not in the direct group ( P = 0·176). There was no mortality and no complications related to either conditioning technique. Conclusion: In this in vivo large-animal model, direct renal artery ischaemic postconditioning protected kidneys against warm ischaemia injury. This straightforward technique could readily be translated into clinical practice.Surgical relevance Ischaemic conditioning has been shown to improve outcomes in both experimental studies and clinical trials in cardiac surgery. Evidence from small-animal and human studies assessing ischaemic conditioning techniques in renal transplantation have not yet established the optimal technique and timing of conditioning. In this study, a large-animal model of renal warm ischaemia was used to compare different conditioning techniques. Postconditioning applied directly to the renal artery was shown to reduce renal injury. Furthermore, new evidence is provided that shorter cycles of ischaemic postconditioning than previously described can protect against renal injury. Evidence from a large-animal model is provided for different conditioning techniques. The beneficial postconditioning technique described is straightforward to perform and provides an alternative method of conditioning following renal transplantation, with potential for application in clinical practice. Abstract : The next step is a clinical RCT